Physical Characterization of Cadmium Sulfide Thin Films Doped with Lithium Deposited Using Spray Pyrolysis Technique (Global Scientific Review, 2024)
The Spray Pyrolysis Technique was utilized to create thin films of both CdS and CdS:Li, with subsequent analysis of their structural, morphological, and optical attributes through X-ray diffraction (XRD), atomic force microscopy (AFM), and UV-visible spectroscopy, respectively. As the proportion of lithium (Li) was increased, there was an observable enlargement in grain size, transitioning from 10.11 nm to 11.07 nm. In parallel, the dislocation density exhibited a decline from 96.83 to 81.58, coupled with a reduction in strain from 34.27 to 31.31. The XRD analysis disclosed a polycrystalline structure with a pronounced alignment along the (111) plane. AFM imaging showcased a spectrum of particle dimensions within the films, ranging from 87.2 nm to 33.14 nm, with higher lithium doping levels of 1% Vol to 3% Vol. Correspondingly, the mean surface roughness (Ra) values experienced a descent from 8.85 nm to 4.34 nm, along with root mean square (RMS) values diminishing from 9.81 nm to 5.55 nm due to the lithium doping